Readmissions in Cancer Patients After Receiving Inpatient Palliative Care in Taiwan: A 9-Year Nationwide Population-Based Cohort Study. Issue 8 (February 2016) - Chang, Hsiao-Ting; Chen, Chun-Ku; Lin, Ming-Hwai; Chou, Pesus; Chen, Tzeng-Ji; Hwang, Shinn-Jang
Abstract : Abstract: Few studies have reported on readmissions among cancer patients receiving inpatient palliative care (IPC). This study investigated readmissions in cancer patients after their first discharge from IPC in Taiwan from 2002 to 2010. This study was a secondary data analysis using information from the National Health Insurance Database in Taiwan from 2002 to 2010. We included subjects ≥20 years old diagnosed with malignant neoplasms who were listed in the registry of catastrophic illness. Patients diagnosed with cancer before January 1, 2002 or who had ever been admitted to an inpatient hospice palliative care unit before the study period were excluded. Readmission was defined as hospital readmission at least once after discharge from first admission to IPC until mortality or the end of the study period. A total of 42, 022 patients who met the inclusion criteria were identified. The majority of these patients were male (60.4%). The mean age of cancer diagnosis was 64.0 ± 14.4 years for men and 64.5 ± 14.7 years for women. The mean age at first hospice ward admission was 65.2 ± 14.2 years for men and 65.9 ± 14.9 years for women. During their first admission to IPC, 59.2% patients died, and the median stay of first IPC admission was 8.0 days. Among those discharged alive from their first admission to IPC, 64.9% were readmitted, and 19.4% of these patients were readmitted on the same day of discharge. From first IPC discharge until mortality, 54.8% of patients were readmitted once, 23.9% were readmitted twice, 9.9% were readmitted 3 times, and 11.5% were readmitted 4 or more times. Being male, having a higher insurance premium level, having a longer length of stay during first IPC admission, being admitted to a teaching hospital, or being admitted to a tertiary hospital increased the adjusted hazard ratio for readmission. We found that terminal cancer patients in Taiwan received relatively late referrals for first admission to IPC and experienced a high rate of readmission after first discharge from IPC. Policies to improve hospice palliative care referrals and decrease readmissions should be considered.